Formulation And Evaluation of Floating Drug Delivery System of Poorly Water Soluble Drug Glipizide - Jakkalwar Shital Madhavrao; Dr. Manish Dubey (Revista Electronica de Veterinaria, 2024)
Floating tablets are a type of gastro-retentive drug delivery system designed to enhance the retention time of dosage forms in the stomach. By prolonging gastric residence, these systems improve the bioavailability of drugs that have a narrow absorption window, exhibit poor solubility in the alkaline environment of the small intestine, or degrade in the intestinal or colonic regions. The key objective in developing oral controlled-release formulations is not merely to extend drug release beyond 12 hours but to ensure the dosage form remains in the stomach or upper gastrointestinal tract until the drug is completely released over the intended duration. Floating tablets are specially formulated to stay buoyant in gastric fluids, enabling a gradual and uniform release of the drug. This characteristic makes them particularly beneficial for medications that require localized or sustained action in the stomach or upper digestive tract. The advancement of floating tablet technology has become a key focus in pharmaceutical research due to its potential to enhance drug delivery and therapeutic effectiveness. These tablets remain in the stomach for an extended period, leading to improved drug absorption, increased bioavailability, and prolonged gastric retention. The principle behind floating tablets involves incorporating agents that promote buoyancy, such as gas-generating compounds or hydrocolloids. Effervescent agents react with gastric fluids to produce carbon dioxide, enabling the tablet to float, while hydrocolloids, including polymers and gelling agents, expand or form a gel-like barrier upon hydration, further aiding flotation. This buoyant nature offers several benefits, primarily ensuring a controlled and sustained release of the drug, helping maintain consistent therapeutic levels in the stomach [1,2].